Komputerowa metoda generowania twarzy na podstawie analizy PCA oraz algorytmu genetycznego - Klosov, Aleksander; Wolan, Łukasz (Face Generating Method Using PCA and Genetic Algorithm, 2006)
The human face image generated on websites by the use of multiuser environment can be applied in face recognition fields, virtual asistents or in computer game design. In the paper the proposition of using evolutionary algorithm and principal components analysis are described. During the evolutionary process users give the personal opinion about one or several faces. The method presents some advantages compared to the traditional face generating methods based on building faces from different parts of 7 to 13 types. Several strategies of users interaction are proposed.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1121, s. 67-85